2021
DOI: 10.3390/ani11082287
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Replacement of Soybean Meal with Fermented Palm Kernel Meal as Protein Source in a Fish Meal-Soybean Meal-Based Diet of Sex Reversed Red Tilapia (Oreochromis niloticus × O. mossambicus)

Abstract: The solid-state fermentation by effective microorganisms (containing photosynthetic bacteria, lactic acid bacteria, nitrogen-fixing bacteria, yeast and Bacillus sp.) improved the nutritive values of palm kernel meal (PKM). Increased crude protein (20.79%), nitrogen-free extract (40.07%) and gross energy (19.58%) were observed in fermented PKM (FPKM) relative to raw PKM while crude lipid (15.65%), crude fiber (36.45%) and ash (29.54%) were decreased. Replacement of soybean meal (SBM) with FPKM as a protein sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The results obtained from this study revealed that the experimental fish utilized the diet very well as observed in the results presented. The result obtained is in line with [35] who reported that sex reversed Red Tilapia (Oereochromis niloticus x Oreochromis mossambicus) can be fed with fermented palm kernel meal as protein source. The results obtained also is in line with [36] who reported better feed conversion ratio, protein efficiency ratio and protein conversion ratio in African catfish fed on fermented Bambara nut meal as substitute of fishmeal.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained from this study revealed that the experimental fish utilized the diet very well as observed in the results presented. The result obtained is in line with [35] who reported that sex reversed Red Tilapia (Oereochromis niloticus x Oreochromis mossambicus) can be fed with fermented palm kernel meal as protein source. The results obtained also is in line with [36] who reported better feed conversion ratio, protein efficiency ratio and protein conversion ratio in African catfish fed on fermented Bambara nut meal as substitute of fishmeal.…”
Section: Discussionsupporting
confidence: 90%
“…The consumption of fermented cottonseed meal increased the diversity and potential functions of the microbiota in the gut. Wattanakul et al, (2021) reported that fish fed with 50% fermented palm kernel meal diet showed the highest overall specific proteolytic activity, followed by fish fed the 75% FPKM diet, indicating a significant capacity to use protein from diets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous phylogenetic analyses revealed that Bacillus velezensis , Bacillus amyloliquefaciens , and Bacillus siamensis clustered tightly to form the “operational group Bacillus amyloliquefaciens ” ( Fan et al, 2017 ), widely used in the food industry and SM fermentation because of their safety and ability to produce proteases. For example, B. amyloliquefaciens ZB has 694 U/g of protease activity and has thus been used for SM fermentation ( Wattanakul et al, 2021 ). The B. siamensis isolate JL8 (protease activity 519·1 U/g) was used in the laboratory production of fermented SM, which showed better properties than unfermented SM ( Zheng et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%